A Discourse of Orientalism in Kelly Yang's Parachutes - Dwi Mery Lidiana; Ikwan Setiawan; Eko Suwargono (Haluan Sastra Budaya, 2024)
This research discusses the construction of orientalism in Parachutes novel. Stereotyping and superiority of the West toward the East were the focuses of the analysis as well as the author’s critical ideology. It applied Edward Said’s orientalism as the underlying theory and qualitative method as the type of the research. Narrative events, dialogues, settings are the collected data for textual analysis. Meanwhile, contextual analysis used related references to strengthen the argument. The result, it was found that orientalism in the form of cultural stereotyping and oppression by the West was still often experienced by Asians as the East in public or in a formal institution. Those related to as the West’s efforts to perpetuated and legitimized their superiority and domination. In addition, internalized orientalism occurs toward Asians society as they always glorified everything about the West.